Analisis Kesalahan Penggunaan Ejaan Bahasa Indonesia Pada Makalah Karya Mahasiswa Universitas Cordova - Mawarni, Heni (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to describe the use of Indonesian Spelling in the papers of Cordova University English Study Program students in semester 2 to describe the errors in the use of Indonesian Spelling in student papers. The object of the study is the analysis of errors in the use of Indonesian Spelling in student papers. Data were taken from students' Indonesian Spelling errors in writing scientific papers. This study is a qualitative descriptive study. Data were collected by observation, documentation, and writing condalingual intralingual methods. The results of this study found several errors in Indonesian Spelling in student papers such as the use of spelling, capital words, prepositions, conjunctions, italics, and prefixes.